Approaches to organization of respiratory tuberculosis detection when its prevalence is decreasing - E. B. Tsybikova; N. A. Zubova (Туберкулез и болезни лёгких)
The objective of the study: to develop a number of organizational measures aimed to improve the eﬀectiveness of early detection and prevention of respiratory tuberculosis among the population including people living with HIV (PLHIV) exposed to tuberculosis infection.Subjects and methods. The authors used data of 34 patients suﬀering from chronic respiratory tuberculosis residing in Saransk; they all had bacterial excretion and were monitored in the TB dispensary in 2015; also, data of 198 respiratory tuberculosis patients residing in Saransk in 2014-2015 were used, these data were obtained from Rosstat Form No. 33 and reporting forms of Edict no. 50 of the Ministry of Health of Russia. For all patients, gender, age, year of birth, address of actual residence (street, house number) are indicated. For the analysis, statistical and cartographic analysis based on geographic information systems (GIS) was used as well as data on the number and density of the population in Saransk, and the type of development in each district of the city. The cartographic web service of OpenStreetMap (OSM) was used as a cartographic basis.Results. The use of a cartographic method based on GIS allowed expanding the concept of a tuberculous nidus setting up buﬀer zones, within which tuberculosis infection also spread as a result of accidental exposure of population to the source of infection. Use of the cartographic method demonstrated that within the buﬀer zones for 1 patient with chronic respiratory tuberculosis with MTB+ there were 4 new tuberculosis patients. To reduce this ratio, multi-level comprehensive organizational measures were developed aimed at the early detection and diagnosis of tuberculosis among population, including PLHIV residing near infection nidi.